2007
DOI: 10.1080/15374410701662766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylphenidate and Behavior Modification on the Social and Academic Behavior of Children With Disruptive Behavior Disorders: The Moderating Role of Callous/Unemotional Traits

Abstract: This study examined whether response to behavior modification with and without methylphenidate differed for children with attention-deficit/hyperactivity disorder (ADHD) and conduct problems (CP) depending on the presence of callous/unemotional (CU) traits. Participants were 37 children ages 7 to 12, including 19 with ADHD/CP-only and 18 with ADHD/CP-CU, referred to a university-based summer treatment program. Results showed that ADHD/CP-CU children had worse behavior in the behavior-therapy-only (BT-only) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 44 publications
8
111
3
2
Order By: Relevance
“…Similarly, in inpatient psychiatric setings, children (ages 7-11) with elevated levels of CU traits had longer length of stay and experienced more physically restrictive interventions during hospitalization [163]. In a school-aged sample of children enrolled in a summer treatment program for externalizing behavior problems, children with children conduct problems and CU traits responded less well to behavior therapy alone than children with conduct problems without CU traits [164] and less improvement in social skills and problem-solving skills when compared to children with CP alone [162]. Hawes and Dadds also found that boys with CU displayed lower treatment response to behavioral parent training and were particularly less responsive to time-outs [165].…”
Section: Treatmentmentioning
confidence: 99%
“…Similarly, in inpatient psychiatric setings, children (ages 7-11) with elevated levels of CU traits had longer length of stay and experienced more physically restrictive interventions during hospitalization [163]. In a school-aged sample of children enrolled in a summer treatment program for externalizing behavior problems, children with children conduct problems and CU traits responded less well to behavior therapy alone than children with conduct problems without CU traits [164] and less improvement in social skills and problem-solving skills when compared to children with CP alone [162]. Hawes and Dadds also found that boys with CU displayed lower treatment response to behavioral parent training and were particularly less responsive to time-outs [165].…”
Section: Treatmentmentioning
confidence: 99%
“…DB tanılı çocuk ve ergenler katı-duygusuz özelliklerin varlığına göre de duygusal, bilişsel ve kişilik özellikleri açısından birbirlerinden farklılık göstermektedir (13). Bu olgularda yapılan katı-duygusuz özelliklerin nörobiyolojisi ve uygun terapötik müdahale ile sosyalizasyon girişimlerinin incelendiği çalışmalarda, olguların önemli bir kısmında kısıtlı prososyal emosyonların olduğu saptanmıştır (14,15). Özellikle katı-duygusuz özellikleri olan alt grup, daha kararlı ve daha şiddetli davranış sorunları, suça yatkınlık ve saldırganlık ile ilişkilendirilmektedir (13).…”
Section: Introductionunclassified
“…Indeed, studies examining the efficacy of typical behavior therapy have shown comparatively reduced positive outcomes for the CP/CU children as compared to CP children without CU traits (CP-only) Waschbusch, Carrey, Willoughby, King & Andrade, 2007). It is hypothesized that that this may be because of a relative under-sensitivity to punishment, and oversensitivity to reward (Lynam, 1998;O'Brien & Frick, 1996).…”
Section: Diagnostic and Statistical Manual Of Mental Disorders (5th Ementioning
confidence: 99%
“…The predictive validity of CU traits for antisocial and disruptive behavior as an antecedent to CD have also been established in child and adolescent samples . Likewise, Waschbusch et al (2007) demonstrated that in an intensive summer treatment program (STP) for children with disruptive behavior disorder, children displaying ADHD with CP/CU displayed increased severity of conduct problems relative to a comparison ADHD/CPonly group. Furthermore, Hawes and Dadds (2007) assert that paucity of positive treatment outcomes are related to stability in levels of CU traits, and find that this is consistent even after controlling for initial CP levels.…”
Section: Cp/cu and Cp-only Differencesmentioning
confidence: 99%